Pemberdayaan Potensi Wisata Alam Air Terjun Curug Lekat Desa Pematang Balam Bengkulu Utara - Febriana, Selvi Eka; Parwito, Parwito; Susilo, Edi; Bastari, Akhmad; Purnawan, Heru; Supriyono, Supriyono (JURNAL BESEMAH, 2022)
The purpose of the empowerment of natural resources and the environment in Pematang Balam village, Hulu Palik sub-district is to increase the potential of nature so that Pematang Balam village can be realized as a wiata village. After a survey was conducted, it turned out that the Pematang Balam village area had a waterfall tour that was not utilized. The method in this activity is to directly visit the waterfall tour of Curug Attached. The target in this activity is a waterfall tour near Pematang Balam village. The result of this activity is that the Pematang Balam village government seeks to increase the potential of the Pematang Balam village area.